Effect of leucine metabolite beta-hydroxy-beta-methylbutyrate on muscle metabolism during resistance exercise training - Nissen, S.; Sharp, R.; Ray, M.; Rathmacher, J. A.; Rice, D.; Fuller, J. C.; Connelly, A. S. (Journal of Applied Physiology, 1996)
The effects of dietary supplementation with the leucine metabolite Beta-hydroxy-Beta-methylbutyrate (HMB) were studied in two experiments. In study 1, subjects (n = 41) were randomized among three levels of HMB supplementation (0, 1.5 or 3.0 g HMB/day) and two protein levels (normal, 117 g/day, or high, 175 g/day) and weight lifted for 1.5 h 3 days/wk for 3 wk. In study 2, subjects (n = 28) were fed either 0 or 3.0 g HMB/day and weight lifted for 2-3 h 6 days/wk for 7 wk. In study 1, HMB significantly decreased the exercise-induced rise in muscle proteolysis as measured by urine 3-methylhistidine during the first 2 wk of exercise (linear decrease, P < 0.04). Plasma creatine phosphokinase was also decreased with HMB supplementation (week 3, linear decrease, P < 0.05). Weight lifted was increased by HMB supplementation when compared with the unsupplemented subjects during each week of the study (linear increase, P < 0.02). In study 2, fat-free mass was significantly increased in HMB-supplemented subjects compared with the unsupplemented group at 2 and 4-6 wk of the study (P < 0.05). In conclusion, supplementation with either 1.5 or 3 g HMB/day can partly prevent exercise-induced proteolysis and/or muscle damage and result in larger gains in muscle function associated with resistance training.